Study on the Multivariant Interactive Teaching Modes of College English under the Information Technology Environment (Informatica, 2019)
Teaching modes can achieve twice the result with half the effort for teaching effect. The multivariant interactive teaching modes based on constructivism theory are a new kind of teaching modes supported by information technology. The multivariant interactive College English teaching modes under the information technology environment has changed the relationship between teachers and students in the classroom teaching process and the relationship between teachers and students and the teaching content. It can improve the quality of English teaching to achieve the goal of effectively improving the teaching effect of the course and improving students' ability of using English language. Based on the background of the information technology environment, this research takes the college students as the object and the multivariant interactive teaching modes as the research method and analyzes the effectiveness of the multivariant interactive teaching modes through an example.